Substituent Effects on Regioselectivity of the Diels-Alder Reactions: Reactions of 10-Allyl-1,8-dichloroanthracene with 2-Chloroacrylonitrile, 1-Cyanovinyl Acetate and Phenyl Vinyl Sulfone - Mujeeb A. Sultan; Usama Karama (Journal of Chemistry)
Diels-Alder reaction of 10-allyl-1,8-dichloroanthracene (3) with 2-chloroacrylonitrile (4) and 1-cyanovinyl acetate (5) gives exclusively the ortho isomer while its reaction with phenyl vinyl sulfone (10) yields a mixture of two isomeric adducts with priority to ortho isomer. The reactions proceeded under microwave condition in xylene. Configurations of these isomers have been assigned with the help of NMR spectra. The results indicated that the steric effect is dominating toward the isomer regioselectivity in the Diels-Alder reaction of the present compounds.